Confocal microscopic analysis of erythrocytes and erythroplastids from Major Mitchell’s cockatoos (Lophochroa leadbeateri) - Clark, Phillip; Raidal, S. (Springer-Verlag London Ltd, 2015)
The majority of avian erythrocytes retain their nucleus throughout the circulatory lifespan of the cell; however, a small proportion of avian erythrocytes are enucleated to form erythroplastids. Previously, we have reported a Major Mitchell’s cockatoo that had a much greater proportion of erythroplastids than typically observed in avian blood. To further classify the erythrocytes of this bird, we employed fluorescent laser scanning confocal microscopy. Fluorescence of the cytoplasm of erythroid cells, including erythroplastids, facilitated assessment including z-stack analysis. Erythroplastids had a mean volume of 118 fL and were predominantly elliptical with minor depressions and infolding of cell surfaces.